Efeito da suplementação com óleo de gergelim (sesamum indicum lim) sobre epileptogênese induzida por pilocarpina em ratos wistar - Silva, Anna Paula Amaro Gervazio da (2017)
Sesame oil (Sesamum indicum Lim) is rich in polyunsaturated fatty acids (PUFAs), which are essential for brain integrity and development, and in natural antioxidants that have anticonvulsive potential in animal models. However, the potential effect of sesame oil on the treatment of refractory epilepsy has been poorly studied. This disease affects patients who do not respond satisfactorily to drug treatment and thus need non-pharmacological strategies such as ketogenic diet and PUFAS. The objective of this study was to investigate the effects of sesame oil supplementation on pilocarpine-induced epileptogenesis. This work was submitted and approved with protocol n ° 002/2016 by the Ethics Committee on the Use of Animals (CEUA). Wistar (Rattus norvegicus) rats were kept under illumination pattern (light/dark cycle, 12/12h) and randomized into five groups with 8 animals each: distilled water (GW), mineral oil (GMO), oil of roasted sesame seeds (RSO), natural sesame oil (NSO) and diazepam (GD). The animals received the substances via orogastric at a dose of 5 ml/kg once daily for 30 days. The GD group consisted of animals that also received distilled water via orogastric and thirty minutes before the induction of status epilepticus, were treated intraperitoneally (i.p.) with diazepam at a dose of 5 mg/kg. On the 31st day, pilocarpine at a dose of 350 mg/kg (i.p.) was used for induction of status epilepticus in all groups. Behavioral changes and seizure intensity were analyzed according to the Racine scale. After the experiment the animals were anesthetized and euthanized by exanguination, the blood was used for biochemical analyzes and the brain was removed for histological analysis. [There was a reduction in feed intake in the RSO groups (148.2 ± 5.2 g, p <0.05) and NSO (137.6 ± 5.9 g, p <0.001) compared to the GW group (GW 166.1 ± 3.5 g) and GMO (171.1 ± 6.1 g). There was no difference (p> 0.05) between the groups in the final weight gain of the animals (GW = 81, 74 ± 8.64 g, GMO = 66.24 ± 9.29 g, RSO = 68.98 ± 5,99 g, NSO = 84.3 6.98 g). In the biochemical tests, the RSO group had lower levels of Cholesterol (58 ± 2.89 mg p <0.05) when compared to the GW group (73 ± 5.91 mg). The NSO group presented lower levels (p <0.05) of triglycerides (59 ± 6.78 mg) and VLDL (11.8 ± 1.35), with an increase in HDL (45 ± 0.96, p <0,05) when compared with the GW group (77.75 ± 5.16, 15.55 ± 1.03, 36.75 ± 2.76, respectively). In the anticonvulsant activity, there was a greater latency time for the appearance of grade 3 of the Racine scale in the RSO groups (533.5 ± 63.21 s, p <0.01) and GD (600.3 ± 61.84 s, p < 0.001) when compared to the GW group (316.9 ± 37.5 s). The NSO and GD groups were able to protect the animals against tonic-clonic and generalized seizures (3178 ± 251.4 s, p <0.01, 3600 ± 0.0 s, p <0.001, respectively) when compared to the group GW (2070 ± 273.3 s). In the histological analysis the GMO group presented a decrease in the number of neuronal cells, disarrangement of the cellular layers and destruction of tissue in the cerebral cortex and hippocampus. While the groups GW, RSO, NSO and GD preserved the organization of the cortical and hippocampal layers, as well as the connections between the neuronal cells]. It is concluded that natural sesame oil has an anticonvulsive and neuroprotective potential and can be used as a coadjuvant in the pharmacological treatment of refractory epilepsy.